Acacia Leaves: A Promising Alternative Feed Source in Addressing Feed Shortages and Enhancing Livestock Productivity - Raju, Sagi; Nagalakshmi, Devanaboyina; Kumari, Nagireddy Nalini; Sravanthi, Boini; Ramyavasavi, Mende; Divya, Begari (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The availability of balanced feed with optimal chemical composition and metabolizable energy (ME) is a significant challenge in ruminant production globally, particularly in India. As the area dedicated to fodder cultivation declines due to competition with cash crops, alternative feed resources, such as tree species, are gaining attention. This study investigates the chemical composition, mineral content, and amino acid profile of Acacia nilotica leaves, which have been identified as a promising alternative feed source for ruminants. Acacia species, known for their resilience in harsh environments, contain high crude protein (17.69%), low detergent fiber, and significant amounts of essential minerals and amino acids, such as glutamic acid, aspartic acid, leucine, and lysine. The leaves are rich in trace minerals like iron, manganese, and zinc, which support various metabolic functions in animals. The study also highlights the suitability of Acaci anilotica leaves as a protein supplement for ruminants, particularly during the dry season when conventional fodder is scarce. The findings suggest that Acacia nilotica leaves have substantial nutritional value, offering an alternative to traditional fodder, with potential benefits for improving livestock productivity and sustainability in ruminant feeding systems.